Software estimation in the maintenance context. - Diev, Sergey (Software engineering notes.)
This article describes an extension of the Use Case Points method of software estimation. The main goal of this extension, called UCPm, is to reflect the specifics of the maintenance phase of software life cycle. UCPm takes into consideration the complexity of the base system. Then, UCPm does not consider the environmental factor as size-contributing entity and defines product size only via unadjusted use case points and technical factor. UCPm also applies four technical factors at the use case level, rather than at the level of the overall product.The method has been applied to more than 30 projects in the course of work on achieving CMM Level 4. It was found that even when requirements are not produced in the use case style, it is relatively easy to build a use case model for the purpose of estimation. It is also believed that the relatively high level of UCP/UCPm reduces the amount of work on estimation. In our preliminary estimates, one use case point maps to approximately four function points.